2002
DOI: 10.1089/08892220260387940
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Antibody-Dependent Cell-Mediated Cytotoxicity (ADCC) in SIV-Infected Macaques Correlates with Delayed Progression to AIDS

Abstract: Although several in vitro lines of evidence support the potential power of antibody-dependent cell-mediated cytotoxicity (ADCC) in controlling HIV infection, the role of ADCC in the pathogenesis of HIV infection in vivo remains uncertain. There are few studies to date that longitudinally determine the plasma ADCC activity in HIV-infected subjects. We sought to establish an SIV/macaque model to perform such a longitudinal study. In the rhesus macaque cohort studied here, three of five macaques (designated Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
87
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 28 publications
(23 reference statements)
2
87
0
Order By: Relevance
“…Several groups also published data suggesting the ability of NK cells to mediate ADCC decreases during HIV infection (11,14,17,22). The association of ADCC with slower disease progression was observed in the rhesus macaque SIV model: maintenance of ADCC activity was observed in slow progressing macaques, and lower plasma ADCC activity was observed in macaques with more rapidly progressing infections (6). Cumulatively, these studies suggest that ADCC could play a pivotal role in slowing disease progression.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Several groups also published data suggesting the ability of NK cells to mediate ADCC decreases during HIV infection (11,14,17,22). The association of ADCC with slower disease progression was observed in the rhesus macaque SIV model: maintenance of ADCC activity was observed in slow progressing macaques, and lower plasma ADCC activity was observed in macaques with more rapidly progressing infections (6). Cumulatively, these studies suggest that ADCC could play a pivotal role in slowing disease progression.…”
Section: Discussionmentioning
confidence: 83%
“…Interest in ADCC has been stimulated by a series of observations implying the involvement of this immune response in the control and prevention of HIV infection. The potential for involvement of ADCC in controlling HIV infection was suggested by observations that Abs capable of mediating ADCC occur at higher titers in HIV-infected elite controllers than in viremic individuals (4), that ADCC Abs in slow progressors (SPs) target a broader range of epitopes than do ADCC Abs from non-SPs (5), and that higher ADCC activity is retained in rhesus macaques with slowly progressing infections with SIV compared with macaques with rapidly progressing infections (6). Furthermore, the potential ability of ADCC to prevent HIV infection was demonstrated by elegant passive-transfer experiments performed in rhesus macaques.…”
mentioning
confidence: 99%
“…Fc-mediated effector functions were found to inversely correlate with viral loads or disease progression in simian immunodeficiency virus (SIV)-infected macaques (39)(40)(41) as well as in HIV-1-infected individuals (42)(43)(44)(45)(46). Furthermore, analysis of correlates of immune protection in the recent RV144 vaccine trial suggested that high levels of ADCC-mediating Abs correlated with decreased HIV-1 acquisition when combined with low plasma IgA anti-Env antibody levels (28,47).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with slow progressing HIV infections also tend to exhibit ADCC-mediating antibodies against a broader range of viral epitopes [9]. Furthermore, a study in SIV-infected macaques linked sustained plasma ADCC activity to slower disease progression [10]. While these studies focused on the ability of anti-viral antibodies to mediate ADCC, other investigators have examined the ability of effector cells, such as natural killer (NK) cells, from HIV-infected individuals to mediate ADCC.…”
Section: Introductionmentioning
confidence: 99%